Study of the Relationship Between Anxiety and Achievement Motivation of Inter-University Level Table Tennis Players: Examining the Correlation Between Anxiety and Achievement Motivation in Inter-University Level Table Tennis Players (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The Purpose of the study was to find outthe relationship between anxiety and achievement motivation of Inter-university level Table TennisPlayers.The subjects of the study were 30 Table Tennis Players (15 males and 15female), who participated in  Inter-University Table Tennis  competition. The hypothesis was that therewill be no signficant relationship between anxiety and achievement Motivation of Table Tennis Players. The data onAnxiety was collected by Administering Sports Competition Anxiety test ByRainer Marten one hour before the competition.However, Achievement Motivationwas collected by Administering Sports Achievement Motivation Test by ML.Kamlesh to the athletes one day before the competition.  Pearson’s Product Moment correlation was usedto find out the relationship between anxiety and achievement.The statisticalanalysis of data revealed that correlation co-efficient between anxiety andachievement Motivation of male Table Tennis Players and female of inter-university level were 0.131 and 0..371, which was not significant at 0.05 levelwith df— 13 as values were lesser than requiredvalue r.05(13) = 0.574